In-depth structural characterization of pentosan polysulfate sodium complex drug using orthogonal analytical tools. (15th April 2020) - Alekseeva, Anna; Raman, Rahul; Eisele, Giorgio; Clark, Thomas; Fisher, Adam; Lee, Sau (Larry); Jiang, Xiaohui; Torri, Giangiacomo; Sasisekharan, Ram; Bertini, Sabrina
Highlights: The combination of several analytical methods to characterize PPS is reported. An in-depth characterization of PPS is reported for the first time. The integrative approach reveals major and minor quality attributes of PPS. This approach represents a tool for comparative studies of Pentosan samples. Abstract: Rapid advances have been made in developing analytical technologies for characterization of highly heterogeneous active ingredients of complex drugs, such as pentosan polysulfate (PPS), active ingredient of the drug Elmiron®, approved by the Food and Drug Administration and marketed in the United States to treat interstitial cystitis. PPS sulfated polysaccharides comprise of a repeat unit of β(1–4)‐D‐xylopyranoses randomly substituted by 4‐O-methyl-glucopyranosyluronic acid. To define the critical quality attributes (CQAs) of such a complex drug, it is critical to develop an approach that integrates data from orthogonal analytical methodologies. Here, we developed an approach integrating diverse analytical tools including gel permeation chromatography, LC/ESI-MS and NMR to measure CQAs of PPS. The proposed mathematical framework integrates the data from these diverse analytical methods as function of PPS chain length and building blocks. Our approach would facilitate in establishing a scientific foundation for comparative characterization of drug products with complex active ingredients.